Research Trends in Digital Financial Inclusion: A Bibliometric Analysis using VoSviewer - Ahiase, Godwin; Umar, Abdurrauf; M. Saeed, Abdulmalek Marwan; Rasuman, Mohammad Abedin; do Rego Tilman Suri, Epifania Rianti (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2024)
Digital financial inclusion (DFI) aims to provide affordable and sustainable financial services to the financially excluded and underserved through cost-effective digital means. This quantitative bibliometric and descriptive research aims to conduct a bibliometric analysis of DFI using VOSviewer software. Data was collected based on the keyword